DYNAMICS OF THE HEART RATE VARIABILITY IN PATIENTS WITH ATRIAL FIBRILLATION DURING ATORVASTATIN THERAPY - E. S. Kozlova; E. E. Galaktionova; F. A. Nemchuk; Yu. M. Lopatin (Столичная издательская компания, 2016)
Aim. To evaluate the heart rate variability (HRV) in patients with ischemic heart disease (IHD) and paroxysmal atrial fibrillation (AF) during atorvastatin therapy.Material and methods. 60 patients with IHD and paroxysmal AF were included in the study. Patients were divided into two groups - control group (basic antiarrhythmic therapy) and second group (basic antiarrhythmic therapy and atorvastatin (Liptonorm, Pharmstandart, Russia) 10mg/day). HRV was compared before and after 3 months of therapy in both groups.Results. Liptonorm significantly improved HRV indices in comparison with basic therapy alone: RMSSD increased on 33% (р <0,02), total power (TP) of spectrum on 28% (р <0,03) and high frequency (HF) component on 53 % (р <0,01).Conclusion. Liptonorm therapy improves autonomic balance in patients with IHD and paroxysmal AF.